PERANCANGAN SISTEM ANTRIAN PEMINJAMAN BUKU DI PERPUSTAKAAN SMKN 1 BUKITTINGGI BERBASIS ANDROID - Elmi Wanti; Riri Okra; Liza Efriyanti; Hari Antoni Musril (KOLONI, 2022)
Queuing is a common occurrence in everyday life, which involves one or two more people, such as waiting in front of the counter to get a train ticket or cinema ticket, at the toll road gate, at the bank, at the library and other situations. which is often encountered, the situation of queuing is not a new thing that we encounter but has become a very common situation that we can encounter in our daily lives. In the real world we are not used to waiting, so it's no wonder we have the opinion that waiting is a tedious job. Very long queues and too long to get a service turn annoying. The book lending queue system is a system that helps the library processor at SMKN 1 Bukittinggi in overcoming long and irregular student queues. The type of research used is R&D (Research and Development) research using the ADDIE version of the development model which consists of several stages, namely Analyze (analysis), Design (design), Develop (development), Implement (implementation), and Evaluate (evaluate). system development model using the System Development Life Cycle (SDLC) by applying the waterfall model consisting of communication, planning, modeling, construction and deployment. The results of product testing that have been carried out with several lecturers, teachers and students, the average value of the validity test is 0.77 (valid), the average practicality test value is 0.77 (high), and the average value of the effectiveness test is is 0.787 (high). The value obtained proves that the loan queuing system can help and is ready to be used. Keywords: Books, queues, Queuing systems for borrowing books.